2004
DOI: 10.1111/j.1349-7006.2004.tb03178.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on cancer immuno‐epidemiology

Abstract: Estimating human cancer risk based on host-environment interaction is one task of epidemiology, and it has provided indispensable knowledge for prevention of cancer. The recent development of gene-engineered mice has also provided solid evidence about the relationship between cancer development and immunity. The aim of this review is to discuss the possible contribution of epidemiology to understanding the role of immunity in host defense against cancer, and also to assess the involvement of inflammation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 50 publications
1
32
1
1
Order By: Relevance
“…Past epidemiologic studies have consistently reported reduced risks of glioma in relation to atopic disease (30), and although causality has not been established, the association might be due to raised tumor immunosurveillance in subjects with allergy (31). Such an effect might also be present for pituitary tumors, although our findings could potentially also be explained by other factors, including selection bias among controls, bias in recall of allergy, and reverse causality.…”
Section: Discussioncontrasting
confidence: 50%
“…Past epidemiologic studies have consistently reported reduced risks of glioma in relation to atopic disease (30), and although causality has not been established, the association might be due to raised tumor immunosurveillance in subjects with allergy (31). Such an effect might also be present for pituitary tumors, although our findings could potentially also be explained by other factors, including selection bias among controls, bias in recall of allergy, and reverse causality.…”
Section: Discussioncontrasting
confidence: 50%
“…Using an 11-year follow-up of this cohort study-where the cytotoxic activity (measured at baseline by the isotope release method using K567 as target cells) was categorized into high, medium, and low levels by tertiles-we previously reported that individuals with high or medium levels of natural cytotoxic activity of peripheral blood lymphocytes had a decreased risk of cancer development compared with those with low cytotoxic activity (6). This was the first evidence of the vital role played by natural immunologic defense in the occurrence of common cancers among the general population (who do not have obvious defects in their immune systems), indicating the possible feasibility of cancer immunoprevention and the usefulness of natural cytotoxic activity as a surrogate biomarker for this prevention (7).…”
Section: Introductionmentioning
confidence: 76%
“…This finding could lead us to a new field, cancer immunoprevention, which would aim to enhance the ability of the immune system to recognize and Research. eliminate nascent transformed cells in the body (7). The innate immune system, in its initial response to a pathogen, may also be involved in determining how long and how strongly inflammation will continue after pathogen infection, in some cases leading to a sequential process of infection to inflammation to cancer (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid regression of a tumor following cytotoxic therapy could lead to a disruption of the tumor niche and subsequent death of the cancer stem cells. For many tumors, there is also an important role played by immune surveillance (Nakachi et al, 2004), and reducing the size of the tumor may allow the immune system to more efficiently eliminate the remaining cells.…”
Section: Inhibiting the Hh/ptch Pathwaymentioning
confidence: 99%